On the Inverse Trace Conversion and maximal informativeness analysis of Japanese internally-headed relative clauses: A reply to Erlewine and Gould 2016. Issue 1 (8th January 2019) - Moulton, Keir; Shimoyama, Junko
In this response to Erlewine & Gould (2016 ), we argue that an account of internally-headed relative clauses using Inverse Trace Conversion and the maximal informativeness semantics for definites of von Fintel et al. (2014 ) does not derive the observed interpretations when the internal head is quantified by certain downward entailing quantifiers and derives no interpretation at all for non-monotonic and some upward entailing quantifiers. We then argue that the cases that Erlewine & Gould (2016 ) claim to be a newly identified interpretation of internally-headed relatives are actually headless relatives.